Colorectal cancers associated with mismatch repair deficiency - Sun, Mingzhu; Monahan, Kevin; Moquet, Jayne; Barnard, Stephen (Frontiers in Medicine, 2025)
This review aims to summarize the latest updates in the prevention, diagnosis, treatment and management of colorectal cancers (CRCs) associated with mutation(s) or alteration(s) in the DNA mismatch repair (MMR) genes. It covers inheritable (Lynch syndrome, constitutional MMR-deficiency syndrome and Familial CRC X) and sporadic CRCs as well as Lynch-like syndrome with both heritable and sporadic features. Despite recommendation for universal testing in all newly diagnosed CRCs, cases with MMR deficiency (dMMR) are still generally underdiagnosed and undertreated in current clinical practice. The distinct molecular and clinicopathologic features of this unique subset of CRC have significant medical importance and have attracted continuous research interest over the years. Updated and currently ongoing research have shown promising results associated with improved clinical outcomes for these patients.